The Impact of Foreign Direct Investment on Palestinian Economic Growth - Hodrob, Rami (International Journal of Economics and Financial Issues, 2017)
Foreign direct investment (FDI) as well as domestic investment and imports are frequently considered as important factors of economic growth in developing countries such as Palestine. This research paper aims to measure and analyze the impact of these factors on Palestinian's economic growth, based on the time series during the period 1995–2014. This has been done through the analysis of the existing causality between FDI, imports and domestic investment on one hand and economic growth on the other hand. Least square method has been adopted to assess these factors on total domestic production of Palestine. The results indicated that FDI has negative impact on Palestinian's economic growth, in contrast to the impact of domestic investment and imports which was investigated to be positive. Keywords: Foreign direct investment (FDI), domestic investment, imports, economic growth, Palestine JEL Classifications: F21, O4